Aktivitas Ekstrak Daun Kemuning (Murraya paniculata (L.) Jack) sebagai Hepatoprotektor pada Tikus yang Terpapar Asap Rokok - Ani Pahriyani; Hadi Sunaryo; Desti Kurnia (Fakultas Farmasi Universitas Setia Budi, 2018)
Cigarettes is a source of free radicals that can cause oxidative stress. It can causefunctional failure of vital organs in the body including the liver that indicated by SGPT andSGOT increment. This research was aimed to observe the activity of 70% ethanol extract ofkemuning leaves (Murraya paniculata (L.) Jack) on SGPT and SGOT digression of male whiterats exposed by cigarette smoke.This research was performed using 25 rats that were divided into 5 groups: normalcontrol (Ko), negative control (Kn), and 3 treatment groups that were given 70% ethanol extractof kemuning leaves with 100 mg / KgBW (K1), 200 mg / KgBW (K2), and 400 mg / KgBW(K3).The SGPT and SGOT levels were analyzed by one-way ANOVA and Tukey test.One-way ANOVA results showed there was a treatment effect on controls (p <0.05).The results of the Tukey showed that the SGPT levels in doses II and III were significantlydifferent from the negative controls but did not differ significantly from the normal controls withlevel value of 34.6 U / L (dose II) and 14.4 U / L (dose III) . At SGOT levels all treatment groupsshowed significantly different comparing to negative controls and not significantly different tonormal controls with level value of 193.6 U / L (dose I), 191.4 U / L (dose II), 156.6 U / L L (doseIII). It can be concluded that 70% ethanol extract of kemuning leaves has activity as ahepatoprotector